The Relationship Of Psychological Burnout To Personality Traits Among Preparatory Section Nannies - غراب رحمة (University of Eloued جامعة الوادي, 2024)
Abstract: The study aims to know the nature of the relationship between psychological burnout and personality traits (extroversion, introversion, poise, and emotionality) and to reveal differences in psychological burnout among nannies due to the personality trait variable . The descriptive approach was used to suit the nature of the study. The sample was from nannies in the preparatory department in the municipality of El-eloued. The researchers selected (35) nannies in a simple random manner . The psychological burnout scale (Seidman and Sanger), translated by Adel Abdullah, and the Eysenck personality scale were applied . The following results were reached: -There is a statistically significant correlation between psychological burnout and personality traits at a significant level. The study also proved that there is a relationship between psychological burnout and the trait of emotional stability . -There is no statistically significant correlation between degrees of psychological burnout and personality traits, as proven by the study - There is no relationship between psychological burnout and the traits of extroversion and introversion.
Keywords: psychological burnout; personality traits